A Review on Toxicity and Challenges in Transferability of Surface-functionalized Metallic Nanoparticles from Animal Models to Humans - Muhammad Arif Asghar (Compuscript Ltd, 2021)
The unique size and surface morphology of nanoparticles (NPs) have substantially influenced all aspects of human life, making nanotechnology a novel and promising field for various applications in biomedical sciences. Metallic NPs have gained immense interest over the last few decades due to their promising optical, electrical, and biological properties. However, the aggregation and the toxic nature of these NPs have restricted their utilization in more optimized applications. The optimum selection of biopolymers and biological macromolecules for surface functionalization of metallic NPs will significantly improve their biological applicability and biocompatibility. The present mini-review attempts to stress the overview of recent strategies involved in surface functionalization of metallic NPs, their specific biomedical applications, and comparison of their in vitro, ex vivo, and in vivo toxicities with non-functionalized metallic NPs. In addition, this review also discusses the various challenges for metallic NPs to undergo human clinical trials.